2002
DOI: 10.1016/s0960-9822(02)00869-2
|View full text |Cite
|
Sign up to set email alerts
|

The Ion Channel Polycystin-2 Is Required for Left-Right Axis Determination in Mice

Abstract: Generation of laterality depends on a pathway which involves the asymmetrically expressed genes nodal, Ebaf, Leftb, and Pitx2. In mouse, node monocilia are required upstream of the nodal cascade. In chick and frog, gap junctions are essential prior to node/organizer formation. It was hypothesized that differential activity of ion channels gives rise to unidirectional transfer through gap junctions, resulting in asymmetric gene expression. PKD2, which if mutated causes autosomal dominant polycystic kidney disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
297
2
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(320 citation statements)
references
References 33 publications
(3 reference statements)
19
297
2
2
Order By: Relevance
“…The gene PKD2, mutations in which cause autosomal dominant PKD and which encodes the calcium release channel polycystin-2, had been shown in a Pkd2 −/− mouse model to represent a master gene regulating left-right axis determination, acting upstream of Nodal, Ebaf, Leftb and Pitx2 (ref. 40). In addition to the malformations described previously 41,42 , homozygous mutant embryos showed right pulmonary isomerism, randomization of embryonic turning, heart looping and abdominal situs inversus.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The gene PKD2, mutations in which cause autosomal dominant PKD and which encodes the calcium release channel polycystin-2, had been shown in a Pkd2 −/− mouse model to represent a master gene regulating left-right axis determination, acting upstream of Nodal, Ebaf, Leftb and Pitx2 (ref. 40). In addition to the malformations described previously 41,42 , homozygous mutant embryos showed right pulmonary isomerism, randomization of embryonic turning, heart looping and abdominal situs inversus.…”
Section: Discussionmentioning
confidence: 52%
“…In mouse, node monocilia are required upstream of the nodal cascade 40 . These findings indicate a strong link between ciliary function and development of laterality.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…A considerable number of studies have reported complete absence of nodal, lefty, or pitx2 expression (Field et al, 2011; Oki et al, 2010; Sakano et al, 2010; Gaio et al, 1999; Takeuchi et al, 2007; Zhang et al, 2001; Yan et al, 1999; Tsukui et al, 1999; Collignon et al, 1996; Kramer-Zucker et al, 2005; Krebs et al, 2003; Pennekamp et al, 2002), with some reporting 100% absent expression for all three genes. What does complete absence of gene expression mean?…”
Section: Discussionmentioning
confidence: 99%
“…While this theory of nodal flow has been widely accepted and modified to include means for both chemical (Nonaka et al, 1998;Okada et al, 2005) and physical (McGrath et al, 2003) modes of generating a left-specific signaling event, other theories have been pre-sented, including a prolonged and stable up-regulation of Ca 2ϩ in the left side of the node, which has been proposed to be involved in regulating the left-sided signaling cascade (McGrath et al, 2003;Tanaka et al, 2005). Mice lacking the membrane cation channel Polycystin-2 (PKD2) have impaired left-right axis determination and do not show left-sided elevation of Ca 2ϩ in the node (Pennekamp et al, 2002;McGrath et al, 2003). Although the mechanism of Ca 2ϩ -dependent regulation of left-right asymmetry remains unclear, work in chick embryos has shown that transient accumulation of extracellular calcium leads to asymmetric activation of Notch (Raya et al, 2004).…”
Section: Introductionmentioning
confidence: 99%